Impact of Asian soybean rust on vegetable soybean, considering two stages of development. (9th January 2023) - Casas‐Leal, Nelson Enrique; Pereira, Fernanda Aparecida Castro; Rocha, Gabriela Antônia de Freitas; Carvalho, Renato Sérgio Batista; Vello, Natal Antônio
Abstract: Diseases can cause negative impacts during all stages of development of soybean [ Glycine max (L.) Merr.] Asian soybean rust (ASR) (caused by Phakopsora pachyrhizi ) is the most destructive. The impact of ASR on vegetable soybean (consumed when the seeds are still immature) have not been studied rigorously. Thus, in a 2‐yr study, we assessed 42 F6 lines from crosses of soybean vegetable genotypes and three commercial cultivars ('BRS 257', 'BRS 267' and 'IAC 100') in two sites. During the R6 and R8 development stages, the genotypes were evaluated for 10 traits. The joint analysis showed that the interactions were significative for the most traits. The significance of the rust effect allowed us to identify the genotypes in which the losses were nonsignificant. We observed that ASR affected two stages of plant development. However, information about ASR losses quantified by the rust reaction rate (RRR) enabled the researchers to select lines that could be used in breeding programs aiming towards ASR tolerance. We found three lines that were superior to one of the cultivar checks. Furthermore, cluster analysis for RRR was useful in establishing the most promising groups of vegetable soybean genotypes for use in hybridization aiming to expand the genetic base for vegetable soybeans and integrate new genetic resources of vegetable soybean in the Brazilian genetic pool to ensure genetic gain. Core Ideas: Asian soybean rust affects the R6 and R8 development stages of vegetable soybean differently. Cluster analysis of the rust reaction rate established genotype groups of vegetable soybean. Three lines of vegetable soybean were superior to one of the cultivar checks.